FENOMENA KOMUNIKASI MAHASISWI LESBIAN LABEL BUTCH DI KOTA PEKANBARU - Muhammad Nanda Saputra; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Sexual deviance lesbian label butch becomes a phenomenon that develop in womanhood, including the student. In fact this phenomenon become a public secret that exist in the campus environment. Until this time lesbian phenomenon so developed with the establishment of organizations that contains a group of people who have sexual orientation deviance in Pekanbaru. This study aims to show the motives, meaning and communication experiences student lesbian label butch in Pekanbaru.This study uses qualitative research with phenomenological approach. The subject of research is consist of five students lesbian label butch Pekanbaru who has been chosen using by the snowball technique. This study used data collection techniques observation, depth interviews, and documentation of research. To achieve the validity of the data this study, researcher used the extension of participation and triangulation.The results showed that the motive student lesbian butch label in Pekanbaru City consists of a motive because (Because motive) that is instinct, a sense of comfort and love and affection. While the motive (in order to motive) which is to be a normal woman. Meanings given by student butch lesbian label is as a life experience, something which is regrettable and destiny to live. The communication experience categorized into two pleasant communication experience in the form of acceptance of character, love one another, a good reception from the surrounding environment and the pleasant treatment. and communication experience unpleasant form of conflict and insults of the family, the conflict in romance, physical abuse of spouses and insults and insults from the environment.Keyword: phenomenon, lesbian, butch, motive, meaning, communication experience